Cephalopod-mimetic tunable photonic coatings assembled from quasi-monodispersed reflectin protein nanoparticles - Loke, Jun Jie (2022)
The remarkable dynamic camouflage ability of cephalopods arises from precisely orchestrated structural changes within their chromatophores and iridophores photonic cells. This mesmerizing color display remains unmatched in synthetic coatings and is regulated by swelling/deswelling of reflectin protein nanoparticles, which alters platelet dimensions in iridophores to control photonic patterns according to Bragg's law. Toward mimicking the photonic response of squid's skin, reflectin proteins from Sepioteuthis lessioniana were sequenced, recombinantly expressed, and self-assembled into spherical nanoparticles by conjugating reflectin B1 with a click chemistry ligand. These quasi-monodisperse nanoparticles can be tuned to any desired size in the 170-1000 nm range. Using Langmuir-Schaefer and drop-cast deposition methods, ligand-conjugated reflectin B1 nanoparticles were immobilized onto azide-functionalized substrates via click chemistry to produce monolayer amorphous photonic structures with tunable structural colors based on average particle size, paving the way for the fabrication of eco-friendly, bioinspired color-changing coatings that mimic cephalopods' dynamic camouflage.